Vaccination against human papillomavirus in Brazilian schoolchildren: National Survey of School Health, 2019 - Isabella de Alcântara Gomes Silva; Ana Carolina Micheletti Gomide Nogueira de Sá; Elton Junio Sady Prates; Deborah Carvalho Malta; Fernanda Penido Matozinhos; Tércia Moreira Ribeiro da Silva (Universidade de São Paulo, 2022)
Abstract Objective: to analyze the prevalence of schoolchildren vaccinated against human papillomavirus (HPV) and the reasons related to non-vaccination. Method: cross-sectional study, with data from the 2019 National Survey of School Health. The sample consisted of 160,721 students aged 13 to 17 years. The prevalence and confidence intervals (95%CI) of vaccinated adolescents were estimated according to location, sex, and administrative dependence of the school. The differences between the strata were evaluated with the Chi-square test. Adjusted prevalence ratios (aPR) and 95%CI were estimated with the Poisson regression model. Results: most of the students were vaccinated (62.9%), and the prevalence of girls (76.1%) was higher than that of boys (49.1%). The most prevalent reason for not vaccinating was "did not know they had to take" (46.8%), with the highest aPR in public schoolchildren in Brazil (1.6; 95%CI 1.5;1.7), from the Northeast region (1.2; 95%CI 1.1;1.2), and in students from private schools in the Northeast regions (1.1; 95%CI 1.1;1.2) and North (1.3; 95%CI 1.2;1.4). Conclusion: one out of every two Brazilian schoolchildren was vaccinated against HPV. Misinformation was a recurring reason for non-vaccination. The North and Northeast regions had the highest prevalence of non-vaccinated people, observed mainly in adolescents from public schools.